2010
DOI: 10.1073/pnas.1001292107
|View full text |Cite
|
Sign up to set email alerts
|

Induced polymerization of mammalian acetyl-CoA carboxylase by MIG12 provides a tertiary level of regulation of fatty acid synthesis

Abstract: Acetyl-CoA carboxylase (ACC), the first committed enzyme in fatty acid (FA) synthesis, is regulated by phosphorylation/dephosphorylation, transcription, and an unusual mechanism of protein polymerization. Polymerization of ACC increases enzymatic activity and is induced in vitro by supraphysiological concentrations of citrate (>5 mM). Here, we show that MIG12, a 22 kDa cytosolic protein of previously unknown function, binds to ACC and lowers the threshold for citrate activation into the physiological range (<1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
137
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(145 citation statements)
references
References 33 publications
2
137
0
1
Order By: Relevance
“…SP1 and SP3 have been found to bind to the promoters of Acly, Acaca, and Fasn, with SP3 stimulating transcription. MIG12 increases the activity of ACACA1 by increasing its polymerization but did not increase protein translation in the liver (19). While we readily detect the ChREBP protein by Western blot in WTLs, we found neither ChREBP protein nor its mRNA in MEC from late-pregnant and lactating mice (M. C. Rudolph and S. M. Anderson, unpublished data), suggesting that it does not regulate lipogenic genes in the lactating alveolar cell.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…SP1 and SP3 have been found to bind to the promoters of Acly, Acaca, and Fasn, with SP3 stimulating transcription. MIG12 increases the activity of ACACA1 by increasing its polymerization but did not increase protein translation in the liver (19). While we readily detect the ChREBP protein by Western blot in WTLs, we found neither ChREBP protein nor its mRNA in MEC from late-pregnant and lactating mice (M. C. Rudolph and S. M. Anderson, unpublished data), suggesting that it does not regulate lipogenic genes in the lactating alveolar cell.…”
Section: Discussionmentioning
confidence: 92%
“…MIG12 is expressed only at low levels in the mammary alveolar cell of mice (P. Ramanathan and M. C. Neville, unpublished observation) and cows (15); so it does not seem to be a candidate for regulation of de novo lactogenesis. The role of THRSP is unclear, but Kim et al (19) found no evidence that it altered polymerization of ACACA1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Spot14-null hepatic de novo fatty acid synthesis was increased 2-fold under lipogenic stimuli, suggesting Spot14 is an inhibitor of this process in the liver ( 40 ). Coexpression of Spot14 with Spot14-R was determined to be inhibitory, as Spot14 heterodimerizes with Spot14-R to prevent Spot14-R association with ACC and decrease activation of the hepatic de novo fatty acid synthesis pathway ( 43 ( 29,41 ). In mammary cancer cells, antisense Spot14 knock down decreased in acetonitrile to initiate derivatization and incubated at room temperature for 30 min ( 50 ).…”
Section: Animalsmentioning
confidence: 99%
“…Signal peptide analysis showed that the MID1IP1 protein is a non-secretory protein. MID1IP1 is a cytoplasmic protein, which has been confirmed in humans and mice (Berit et al, 2004;Kim et al, 2010). To further investigate the detailed structure of porcine MID1IP1, SABLE on-line analysis software was employed to determine secondary structure.…”
Section: Discussionmentioning
confidence: 99%